54P Applicability of the LIPI score to metastatic microsatellite instability high cancer patients treated with immune checkpoint inhibitors. (15th December 2019) - Vuagnat, P; Auclin, E; Mezquita, L; Alfonso, J Adeva; Tocino, M R Vidal; Munoz, F Longo; El Dakdouki, Y; Romano, P Martin; Baldini, C; Varga, A; Garcia-Carbonero, R; Besse, B; et al.
Abstract: Background: Microsatellite instability high (MSI-H) is an approved tissue-agnostic predictive biomarker of benefit to immune checkpoint inhibitors (ICI). However not all patients (pts) respond to ICI and additional biomarker of response in this population is still required. The Lung-Immune Prognostic Index (LIPI), combining derived NLR (dNLR=neutrophils/[leucocytes-neutrophils]) and lactate dehydrogenase (LDH) demonstrated a strong correlation with ICI outcomes in NSCLC and other tumor types. We aimed to evaluate the value of pretreatment LIPI for predicting benefit to ICI in MSI-H population. Methods: We performed a multicenter retrospective study of pts with metastatic MSI-H tumors treated with ICI from Apr 2014 to May 2019. Biological and clinical data were retrospectively collected and LIPI was calculated based as previously reported. LIPI groups were: good (dNLR≤3 + LDH≤upper limit of normality [ULN]), intermediate (dNLR>3 or LDH>ULN and poor (dNLR>3+LDH>ULN). The primary endpoint was progression-free survival (PFS) and secondary endpoints were overall survival (OS), overall response rate (ORR). Results: Preliminary data is available for 111 pts, with the following characteristics: 43 (39%) male; median age of 62 (24-93), median number of previous lines 1 (range 0 – 6); most common tumor types were colorectal (43%) and endometrial cancer (15%). MSI was defined by immunochemistry and/or polymerase chain reaction (PCR) in 88% and 37 pts (38%) had a confirmed Lynch Syndrome. 98 pts (88%) were treated with a single agent-PD(L)1 inhibitor. The median (m) PFS was 14.1 months (m.) [95%CI, 8.38-not reached (NR)] and the mOS was NR [95%CI, 30-xx] with 44% of ORR. LIPI stratified the population in: good (51, 46%), intermediate (50, 45%) and poor groups (10, 9%). The good group had mPFS of 20.9m. vs. 32m. for intermediate vs. 1.8m. for poor groups (P = 0.0006). In the good group, the ORR was 55% vs. 38% for intermediate vs. 13% in poor group (P = 0.05). OS data are not mature yet. Conclusion: Poor LIPI is correlated with worse ICI outcomes (PFS, ORR) in MSI-H pts, identifying potentially a MSI-H subset of pts with no benefit from ICI. This study is still ongoing for assessing the value of LIPI in a larger cohort. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: P. Vuagnat: Research grant / Funding (institution), Full / Part-time employment, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche, Sanofi: As part of the Drug Development Department (DITEP); Non-remunerated activity/ies, AstraZeneca, Bayer, Bristol-Myers Squibb, Boringher Ingelheim, Johnson & Johnson, Lilly, Medimmune, Merck, NH TherAGuiX, Pfizer, Roche: As part of the Drug Development Department (DITEP). E. Auclin: Travel / Accommodation / Expenses: MundiPharma; Speaker Bureau / Expert testimony: Sanofi Genzyme. L. Mezquita: Advisory / Consultancy: Roche; Speaker Bureau / Expert testimony: Bristol-Myers Squibb, Tecnofarma, Roche, AstraZeneca; Travel / Accommodation / Expenses: Bristol-Myers Squibb, Roche, Chugai. M.R. Vidal Tocino: Advisory / Consultancy: Amgen, Celgene, Merck, Sanofi; Travel / Accommodation / Expenses: Amgen, Roche. P. Martin Romano: Research grant / Funding (institution), Full / Part-time employment, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche, Sanofi: As part of the Drug Development Department (DITEP); Non-remunerated activity/ies, AstraZeneca, Bayer, Bristol-Myers Squibb, Boringher Ingelheim, Johnson & Johnson, Lilly, Medimmune, Merck, NH TherAGuiX, Pfizer, Roche: As part of the Drug Development Department (DITEP). C. Baldini: Research grant / Funding (institution), Full / Part-time employment, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche, Sanofi: As part of the Drug Development Department (DITEP); Non-remunerated activity/ies, AstraZeneca, Bayer, Bristol-Myers Squibb, Boringher Ingelheim, Johnson & Johnson, Lilly, Medimmune, Merck, NH TherAGuiX, Pfizer, Roche: As part of the Drug Development Department (DITEP). A. Varga: Research grant / Funding (institution), Full / Part-time employment, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche, Sanofi: As part of the Drug Development Department (DITEP); Non-remunerated activity/ies, AstraZeneca, Bayer, Bristol-Myers Squibb, Boringher Ingelheim, Johnson & Johnson, Lilly, Medimmune, Merck, NH TherAGuiX, Pfizer, Roche: As part of the Drug Development Department (DITEP). B. Besse: Research grant / Funding (institution): Bristol-Myers Squibb, Roche, Chugai. C. Massard: Research grant / Funding (institution), Full / Part-time employment, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche, Sanofi: As part of the Drug Development Department (DITEP); Non-remunerated activity/ies, Amgen, Astellas, AstraZeneca, Bayer, BeiGene, Bristol-Myers Squibb, Celgene, Debiopharm, Genentech, Ipsen, Janssen, Lilly, MedImmune, Novartis, Pfizer, Roche, Sanofi, Orion: Consultant/Advisory fees. A. Hollebecque: Research grant / Funding (institution), Full / Part-time employment, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche, Sanofi: As part of the Drug Development Department (DITEP); Non-remunerated activity/ies, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche, Sanofi: As part of the Drug Development Department (DITEP). All other authors have declared no conflicts of interest.